Another Gaze 05. - Shreir, Daniella; Williams, Missouri; Makary, J; da Costa, Cassie (London : Another Gaze, 2021)
Palacios Cruz, Maria ; Mcllwain, Maeve ; Collee, Lauren ; saheli singh, sava ; Dolbear, Sam ; Groom, Amelia ; Ty, M. ; El-Enany, Nadine ; Aumiller, Rachel ; Nicastro, Clio ; Sunhyun Mischaelsen, Anja ; Carr, Georgie ; Russell, Nicholas ; Stocker, Octavia ; Hamrah, A.S. ; Price, Yasmina ; Oliveira, Janaina ; Ellerson, Beti ; Konaté, Awa ; Bodomo, Nuotama Frances ; Grimaldi Donahue, Allsion ; Kirkland, Katie ; Borden, Lizzie ; Scanlan, Kathryn ; Messerschmidt, Sarah ; da Costa, Cassie ; Campion, Phoebe ; Scherffig, Clara Miranda ; Rubinstein, Bessie ; Liu, Rebecca ; Staab, Laura ; K. Moselle ; roselman, james ; Fletcher, Richard ; Beauvais, Frank ; Rangan, Pooja ; Warren, Shilyh ; Stephens, Courtney
A journal of film and feminisim
boek